Update on Infections in Primary Antibody Deficiencies - Demirdag, Yesim Yilmaz; Gupta, Sudhir (Frontiers in Immunology, 2021)
Bacterial respiratory tract infections are the hallmark of primary antibody deficiencies (PADs). Because they are also among the most common infections in healthy individuals, PADs are usually overlooked in these patients. Careful evaluation of the history, including frequency, chronicity, and presence of other infections would help suspect PADs. This review will focus on infections in relatively common PADs, discussing diagnostic challenges, and some management strategies to prevent infections.